1954
DOI: 10.1161/01.res.2.6.565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blood and Saline Infusion on Cardiac Performance in Normal Dogs and Dogs with Arteriovenous Fistulas

Abstract: Maximum left ventricular work response (and other hemodynamic changes) to infusion of saline and whole blood was compared in normal dogs and in dogs with aorta-caval and multiple peripheral fistulas. In the dogs with fistulas the augmented preinfusion levels of cardiac work and left ventricular end-diastolic pressure approximated those in normal dogs after maximum response to infusion. Following infusion in the dogs with fistulas, end-diastolic pressure characteristically increased but cardiac work did not. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0

Year Published

1957
1957
1996
1996

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 5 publications
3
16
0
Order By: Relevance
“…Some animals developed edema of the fore-limbs as well as the hind-limbs, and a number of the dogs died of pulmonary edema which is highly indicative of cardiac failure under these circumstances. The maximum cardiac work levels in these preparations were similar to those obtained in normal dogs with massive infusion of blood or saline (1). The left ventricular end-diastolic pressure was consistently elevated in the fistula group, the lowest value being 13 mm.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Some animals developed edema of the fore-limbs as well as the hind-limbs, and a number of the dogs died of pulmonary edema which is highly indicative of cardiac failure under these circumstances. The maximum cardiac work levels in these preparations were similar to those obtained in normal dogs with massive infusion of blood or saline (1). The left ventricular end-diastolic pressure was consistently elevated in the fistula group, the lowest value being 13 mm.…”
Section: Discussionsupporting
confidence: 80%
“…Previous work has demonstrated that a severe burden is placed on the circulatory system of the dog by the surgical production of a long-sustained aortic-caval fistula (1). Circulatory distress is manifested by ascites, edema of all extremities and the lungs, together with a marked rise in left ventricular end-diastolic pressure, cardiac output, cardiac work, heart rate, and a depression of total peripheral resistance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In man the cardiac output, heart rate, and right atrial pressure are elevated, arterial pulse pressure is increased (1)(2)(3)(4), and the blood volume is expanded (5). Similar effects have been observed in the dog with an experimentally induced fistula (6)(7)(8)(9)(10), and a reduction in peripheral blood flow (7) and renal blood flow (10) also has been observed. In addition, maximum cardiac output, attainable by transfusion, may be greater in dogs with an arteriovenous shunt than in normal dogs, whereas the maximum stroke work is less (8).…”
Section: Introductionmentioning
confidence: 62%